Assessment of the Chesapeake Bay watershed socio-ecological system through the Circles of Coastal Sustainability framework - Leyva Ollivier, María Esther; Newton, Alice; Kelsey, Heath (Frontiers in Water, 2024)
The concern with preserving natural resources for the future has been capturing global attention due to the state of decline of productive ecosystems. Chesapeake Bay, a large estuary located on the mid-Atlantic coast of the United States of America is such a productive ecosystem supporting thousands of animal and plants species, and the surrounding human population. Despite the concept of sustainable development, there has been continued pressure on the natural resources and the ecosystem services of the Bay. Institutional restoration and management efforts have been extensive, generating organizations, agreements, regulations and projects, among others. This research assesses Chesapeake Bay’s sustainability in four domains: environment, social, economy, and governance, using the Circles of Coastal Sustainability methodology. Each of the four domains has five categories, and each category is evaluated by the authors’ expert judgment using indicators related to the socio-ecological system and the definition of sustainable development. The article proposes a global sustainability score developed by a literature review of sustainability evaluated through the expert judgment of the authors. The results from the framework gave a “Satisfactory” score to the overall system; the environment and economic domains obtained the “Satisfactory” score, whilst the government and social domains obtained “Good” and “Poor” scores, respectively. The categories ranged between “Excellent” and “Poor” scores. The “Excellent” score was obtained by organization. The “Poor” score was obtained by five categories across the domains including social benefits, demographic, identity, security, and economic wellbeing. The assessment showed that the system has degradation problems, but the results have provided a general foundation for management bridges and barriers for sustainable development, with the barriers used to discuss new bridges towards holistic management proposals. The framework is a tool in progress to communicate to various actors the current sustainability development with the available information, provide a holistic system view, and find knowledge gaps in the research of a system. Similarly, the framework and assessment can be complemented, adapted, refined, and improved with each application as part of an adaptive management iterative cycle.